2017
DOI: 10.1071/rd16174
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid reverses the effects of metronidazole-induced infertility in male albino rats

Abstract: Rosmarinic acid (RA) is a natural antioxidant that has many biological activities. In the present study we investigated the potential of RA to reverse the negative effects of the widely used antibiotic and antiprotozoal agent metronidazole (MTZ), which is known to induce reversible male infertility. Two doses of RA (5 and 15mg kg) were studied in sexually mature rats with and without MTZ-induced infertility. Rats were intraperitoneally injected with 5mg kg RA or 15mg kg RA (in distilled water) and, 45min later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…RA is a water-soluble polyphenolic phytochemical with free-radical scavenging and antioxidant effects (Veras et al, 2019). Al-Alami et al (2017) showed that RA had a reversal effect on metronidazole-induced infertility in male albino rats. In the present study, tegrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA is a water-soluble polyphenolic phytochemical with free-radical scavenging and antioxidant effects (Veras et al, 2019). Al-Alami et al (2017) showed that RA had a reversal effect on metronidazole-induced infertility in male albino rats. In the present study, tegrity.…”
Section: Discussionmentioning
confidence: 99%
“…Al‐Alami et al. (2017) showed that RA had a reversal effect on metronidazole‐induced infertility in male albino rats. In the present study, supplementation of RA in the extender effectively improved stored boar sperm motility, plasma membrane integrity and acrosomal integrity.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with those of many researchers. 4,13,15,26,[30][31][32] These spermatotoxic effects of MTZ can be partially explained by the fact that MTZ crosses the BTB and negatively affects the germ cells in the seminiferous tubules, with subsequent decreased secretion of testosterone. 15,32 However, the mechanism of the inhibitory effect of MTZ on reproductive hormones (gonadotrophins and testosterone) is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, prolonged MTZ therapy was shown to induce reversible, unwanted effects on male fertility, reproductive hormone levels and sperm motility and/ or the sperm count. [2][3][4] This MTZ-induced infertility has been shown to be prevented by supplementation with natural compounds that are known to have antioxidant activity. 3,4 MTZ-associated neurotoxicity has been reported in both humans and veterinary species, including rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation